Factors Influencing the Intention to Use Private Autonomous Vehicles in Indonesia's Big Cities - Nuriayani, Endang; Ekaputra, Donny; Afiani, Feny Fitria (LP3M Universitas Putra Bangsa, 2024)
This research explored the factors influencing the intention to use Private Autonomous Vehicles (PAVs) in Indonesia's big cities. The Technology Acceptance Model (TAM) was employed as the theoretical framework due to its model explaining the adoption of new technologies. The study utilized a quantitative approach, employing a Google Form questionnaire to collect data from 315 respondents in Jakarta, Bogor, Depok, Tangerang, and Bekasi. The data were analyzed using PLS-SEM analysis. While previous studies focused on AV adoption in Indonesia, particularly shared AVs as public transportation, and overlooked the aspect of AV familiarity concerning private AV adoption, this research addressed these gaps. The study's novelty lies in including AV familiarity and facilitating conditions variables. The study found that safety, AV familiarity, and facilitating conditions significantly impacted the perceived usefulness and ease of use of AVs, while personal benefit and social influence did not. In conclusion, adapting marketing strategies to diverse user preferences, emphasizing safety in promotional materials, strengthening educational efforts, seeking government support for road improvements, and enhancing the perceived ease of use and usefulness are essential to fostering positive attitudes and intentions toward autonomous vehicle technology.